2018
DOI: 10.1002/jcb.27333
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of resveratrol on human T‐ALL cell line CCRF‐CEM is unlikely exerted through alteration of BAX and BCL2 promoter methylation

Abstract: One of the fundamental barriers leading to failure of leukemia therapy is the resistance against conventional chemotherapies, common modality used to cure leukemia. Having the potential to trigger apoptosis in various human leukemia cell lines, resveratrol is regarded as a robust agent in chemotherapy regimens. The current study was aimed to assess whether the apoptotic effect of resveratrol on T-cell acute lymphoblastic leukemia cell line, CCRF-CEM, is exerted through DNA methylation of BAX and BCL2 gene prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The BAG family was first identified as a group of proteins that prevent cell death through their interaction with Bcl-2 (20). The Bcl-2 family genes (Bcl-2 and Bax) play critical roles in the apoptosis of T-ALL cells (41,42). In the present study, the results also demonstrated that the protein expression levels of Bcl-2 were decreased and the levels of Bax were increased simultaneously following the downregulation of the levels of BAG2.…”
Section: Discussionsupporting
confidence: 68%
“…The BAG family was first identified as a group of proteins that prevent cell death through their interaction with Bcl-2 (20). The Bcl-2 family genes (Bcl-2 and Bax) play critical roles in the apoptosis of T-ALL cells (41,42). In the present study, the results also demonstrated that the protein expression levels of Bcl-2 were decreased and the levels of Bax were increased simultaneously following the downregulation of the levels of BAG2.…”
Section: Discussionsupporting
confidence: 68%
“…Zadi Heydarabad and colleagues showed that DNA methylation of BAX and BCL2 genes in a T-cell acute lymphoblastic leukemia cell line, CCRF-CEM, can be detected after resveratrol treatment by a methylation-specific polymerase chain reaction technique. They suggested that this observation might explain the effect of resveratrol in sensitizing ALL cells to apoptosis [ 131 ]. In another study, the effect of resveratrol on retinoic acid resistance in the anaplastic thyroid cancer cell line THJ-11T and the human medulloblastoma UW228-2 cell line showed that resveratrol not only demethylates the cellular retinoic acid binding protein 2 (CRABP2) promotor but also decreases the amounts of some DNA methyltransferases such as DNMT1, 3A, and 3B [ 132 ].…”
Section: Polyphenols Modulate Cancer Drug Resistancementioning
confidence: 99%
“…Resveratrol is a natural polyphenol compound with a variety of biological activities, such as antioxidant, anti-inflammatory, immunoregulatory, chemopreventive and antitumor activities (19). Resveratrol treatment has been shown to trigger the apoptosis of the T-acute lymphoblastic leukemia (T-ALL) cell line, ccRF-cEM, via the upregulation of the apoptotic BAX gene and the downregulation of the anti-apoptotic BcL2 gene (20). Apoptosis has also been shown to be induced in TRAIL-resistant lung cancer cells following co-treatment with resveratrol and TRAIL via the suppression of Akt/NF-κB signaling (21).…”
Section: Resveratrol Inhibits the Progression Of Cervical Cancer By Smentioning
confidence: 99%